Enabling the uptake of circular water solutions - Frijns, Jos; Smith, Heather M.; Makropoulos, Christos (IWA Publishing, 2024)
This study advances the discourse on the transition from a linear to a circular water paradigm, within which water is reused and resources such as nutrients and energy can be recovered. The research provides an empirical evidence from demonstrative cases, identifying the technological, economic, socio-cultural, and regulatory factors that facilitate or impede the broader adoption of circular solutions in the water sector. It proposes an integrated system approach, which encompasses a comprehensive set of enabling instruments, including (a) the demonstration of the sustainability of circular water technologies at a system level, thereby providing a robust proof of concept; (b) a shift from a conventional financial cost-benefit approach to a business model predicated on circular value chains, underscoring the economic feasibility of these solutions; (c) the enhancement of social acceptance through active stakeholder engagement, thereby fostering a supportive community for these transformative changes; and (d) the adaptation of the regulatory framework to incentivise circular water solutions, such as the establishment of dedicated end-of-waste criteria to facilitate market access for recovered resources. The study concludes that a concerted effort is required to reconceptualise our water systems as circular systems, and to legitimise the role of circular water within our society and economy.
Keywords: Circular water governance; Circular water systems; Regulations; Societal acceptance; Value chains; Wastewater resource recovery